Preparation method and application of ultrathin hydrophobic zinc-loving artificial solid protective layer

By using FeHCF nanomembrane in zinc-based batteries to build an ultra-thin, waterproof, Zn2+ selective protective layer, the problem that the interface water layer between the zinc negative electrode and the electrolyte cannot be eliminated is solved, and the performance improvement and safety guarantee of zinc-based batteries are achieved.

CN119812181AActive Publication Date: 2025-04-11JILIN UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510015862.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The prior art cannot build ultra-thin, waterproof, Zn2+ selective nano films, resulting in the inability to effectively eliminate the water layer between the zinc negative electrode and the electrolyte interface, which in turn affects the performance and safety of zinc-based batteries.

Method used

FeHCF nanofilm is used as an ultra-thin hydrophobic zinc-friendly artificial solid protective layer. By forming the FeHCF nanofilm at the air-water interface and transferring it to the surface of the zinc negative electrode, an ultra-thin (about 16.9nm), waterproof, Zn2+ selective protective layer is constructed.

Benefits of technology

It effectively eliminates the water layer at the interface between the zinc negative electrode and the electrolyte, inhibits hydrogen evolution and corrosion reactions, improves the Coulomb efficiency and cycle life of zinc-based batteries, and ensures the stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812181A_ABST
    Figure CN119812181A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an ultrathin hydrophobic zinc-loving artificial solid protection layer, and belongs to the field of aqueous zinc ion batteries. The invention aims to solve the problems that an ultrathin, waterproof and Zn < 2 + > selective nano film cannot be constructed and a water layer between a zinc negative electrode and an electrolyte interface cannot be eliminated in the prior art. The method comprises the following steps: 1, preparing a FeHCF nano film; and 2, transferring the FeHCF nano film. According to the application, the material is used as a protective layer of a zinc negative electrode in a water-based zinc ion battery. The invention is used for preparation and application of the ultrathin hydrophobic zinc-loving artificial solid protective layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aqueous zinc ion batteries. Background Art

[0002] Aqueous zinc metal batteries (AZMBs) hold great promise as cost-effective, intrinsically safe, and environmentally benign energy storage systems. However, the practical application of AZMBs is severely hampered by the instability of the zinc metal anode. In commonly used weakly acidic aqueous electrolytes, the zinc anode suffers from uncontrolled dendrite growth and side reactions, resulting in reduced coulombic efficiency, shortened cycle life, and safety issues, thus hindering the realization of high-performance zinc-based batteries.

[0003] One of the main challenges facing Zn anodes comes from water-related reactions such as the hydrogen evolution reaction (HER). 2+ ) occurs at a relatively low potential (-0.76 V vs. SHE), which is much lower than the standard hydrogen evolution potential. However, in weakly acidic electrolytes, the competition between zinc deposition and HER is quite serious. During zinc deposition, protons react with Zn 2+ enter the negative electrode surface together and are reduced to hydrogen (i.e. 2H + +2e - →H2). In addition, the vertical growth of zinc dendrites will expose more HER active sites. The HER on the negative electrode surface is largely dependent on the water structure at the interface. It is reported that the solvation structure in the outer Helmholtz layer plays an important role in regulating the HER activity on the electrode surface. Guided by this principle, various strategies such as high-concentration electrolytes, ionic liquids, water-poor hydrogels, and hydrophobic organics are used to regulate the electrical double layer. These strategies have proven to be successful in reducing the water activity at the interface. However, in order to exclude the possible existence of HER at the interface, the unwanted water layer at the electrode interface should be completely eliminated. Therefore, it is very necessary to achieve direct solid-solid contact between the electrode and the electrolyte to prevent the formation of a water layer on the negative electrode surface. At the same time, the electrode interface is very sensitive to the fast Zn 2+ The transport should show ion selectivity. However, the common electrode interface protective layer will gradually absorb and diffuse water in the protective layer, which inevitably leads to the formation of an ultra-thin water layer. Therefore, how to construct an ultra-thin, waterproof, Zn 2+ Selective nanomembrane to eliminate the water layer between the zinc negative electrode and the electrolyte interface is a technical difficulty that needs to be urgently solved by existing technologies. Summary of the invention

[0004] The present invention aims to solve the problem that the existing technology cannot construct ultra-thin, waterproof, Zn 2+ The selective nanofilm eliminates the problem of the water layer between the zinc negative electrode and the electrolyte interface, thereby providing a preparation method and application of an ultra-thin hydrophobic zinc-philic artificial solid protective layer.

[0005] A method for preparing an ultra-thin hydrophobic zinc-philic artificial solid protective layer is carried out according to the following steps:

[0006] 1. Preparation of FeHCF nanofilm:

[0007] The potassium ferricyanide aqueous solution is mixed with deionized water, and the dioctadecyl dimethyl ammonium bromide chloroform solution is dispersed on the liquid surface and allowed to stand to form a surfactant layer at the air-water interface, and then the ferric chloride aqueous solution is added dropwise to the solution below the surfactant layer, and reacted at room temperature to form a FeHCF nanofilm at the air-water interface, thereby obtaining a liquid containing the FeHCF nanofilm;

[0008] 2. Transfer of FeHCF nanofilm:

[0009] The substrate is vertically immersed in a liquid containing the FeHCF nanofilm, and then the substrate is slowly lifted, the FeHCF nanofilm formed at the air-water interface is transferred to the substrate, and finally dried, thereby completing the preparation method of the ultra-thin hydrophobic zinc-philic artificial solid protective layer.

[0010] Application of ultrathin hydrophobic zinc-philic artificial solid protective layer, which is used as the protective layer of zinc negative electrode in aqueous zinc-ion batteries.

[0011] The beneficial effects of the present invention are:

[0012] The present invention provides a new method for stabilizing the zinc metal negative electrode by constructing an ultra-thin (~16.9nm) Zn metal negative electrode composed of dioctadecyl dimethyl ammonium bromide (DODA) and FeHCF. 2+ Selective and water-repellent layer. This interface engineering strategy effectively eliminates the electrode interface water layer, inhibits hydrogen evolution and corrosion, and thus overcomes the long-standing obstacle to the development of aqueous zinc batteries. The "Faraday cation pumping" mechanism generated within the FeHCF nanomembrane ensures fast and selective Zn 2+ transport while maintaining negligible water permeation, thus creating a stable, dendrite-free environment.

[0013] Instruction Manual

[0014] Figure 1 The actual picture of the FeHCF nanofilm formed at the air-water interface in step 1 of Example 2, a is the overall actual picture, and b is a local enlarged picture of the edge of the FeHCF nanofilm;

[0015] Figure 2 Optical microscope and transmission electron microscope images of the FeHCF nanofilm prepared in step 1 of Example 1, (a) optical microscope image, (b) transmission electron microscope image;

[0016] Figure 3The XRD pattern and TEM high-resolution image of the FeHCF nanofilm prepared in step 1 of Example 1, (a) XRD image, (b) TEM high-resolution image, and the inset is the electron diffraction pattern;

[0017] Figure 4 The element distribution map, AFM map, Raman map, and XPS full spectrum map of the FeHCF nanofilm prepared in step 1 of Example 1 are shown in Figures 1 and 2. (a) element distribution image, (b) AFM image, (c) Raman image, and (d) XPS full spectrum map.

[0018] Figure 5 Infrared images and contact angle images, (a) infrared image of the FeHCF nanofilm prepared in step 1 of Example 1, (b) contact angle comparison of the zinc sheet covered with the ultra-thin hydrophobic zinc-philic artificial solid protective layer prepared in Example 1 and bare Zn;

[0019] Figure 6 This is a comparison chart of the deposition / stripping coulombic efficiency test of the Zn||Cu half-cell assembled in Example 3 and Comparative Experiment 1. a is the value at 10 mA / cm 2 and 1mAh / cm 2 CE diagram of Zn||Cu half-cell, b is at 5mA / cm 2 and 1mAh / cm 2 CE diagram of Zn||Cu half-cell when ;

[0020] Figure 7 At 10mA / cm 2 and 1mAh / cm 2 When , the voltage distribution comparison diagram of the Zn||Cu half-cell assembled in Example 3 and Comparative Experiment 1, a is Example 3, b is Comparative Experiment 1;

[0021] Figure 8 This is a comparison chart of the cycle test of the Zn||Zn symmetric battery assembled by transferring the FeHCF nanofilm to zinc foil in Example 4 and Comparative Experiment 2, a at 1 mA / cm 2 and 1mAh / cm 2 Cyclic performance under 2 mA / cm 2 and 10mAh / cm 2 DOD cycle performance under ;

[0022] Fig. 9 In-situ optical microscope images of zinc deposition / stripping of FeHCF / Cu and bare Cu after cycling of the Zn||Cu half-cell assembled in Example 3 and Comparative Experiment 1, a is bare Cu, b is FeHCF / Cu;

[0023] Fig.10The thickness of zinc deposited on FeHCF / Cu and bare Cu and the deposition / stripping time after cycling of the Zn||Cu half-cell assembled in Example 3 and Comparative Experiment 1;

[0024] Fig.11 Figure 3 is a graph showing the morphology and mechanical strength test of zinc foil after deposition of FeHCF nanofilms prepared in Example 1 attached to titanium foil (experimental group) and pure titanium foil (control group); a is a schematic diagram and a physical picture showing the peeling of zinc foil deposited on the surface of titanium foil in the experimental group; b is a physical picture showing the peeling of a large area (10 cm×10 cm) of zinc foil deposited on the surface of titanium foil in the experimental group; c is a physical picture showing the peeling of zinc foil deposited on the surface of titanium foil in the experimental group and folding; d is a physical picture showing the peeling of zinc foil deposited on the surface of titanium foil in the control group and folding;

[0025] Fig.12 The scanning electron microscope images of the negative electrode of the Zn||Zn symmetric battery assembled in Example 4 and Comparative Experiment 2 after cycling, a and b are for Example 4, c and d are for Comparative Experiment 2;

[0026] Fig.13 Reversible color change of zinc foil attached with FeHCF powder prepared in Example 1 during zinc deposition and stripping; a is uncycled; b is 2.5 mA-hours of deposition at a current of 20 mA; c is 5 mA-hours of deposition at a current of 20 mA; d is 5 mA-hours of deposition followed by 2.5 mA-hours of stripping at a current of 20 mA; e is 5 mA-hours of deposition followed by 5 mA-hours of stripping at a current of 20 mA;

[0027] Fig.14 The XPS spectra of FeHCF prepared in Example 1 during zinc deposition and stripping and the Fe 2p XPS spectra of the FeHCF nanofilm without circulation, a is FeHCF after 15 minutes of deposition, b is FeHCF after 15 minutes of deposition and then stripping for 15 minutes, c is the Fe 2p XPS spectrum of the FeHCF nanofilm prepared in step 1 of Example 1 without circulation;

[0028] Fig.15 XRD diagram, theoretically calculated electrostatic potential diagram and theoretically calculated electric field distribution of the negative electrode of the Zn||Zn symmetrical battery assembled in Example 4 after charge and discharge cycles; a is the XRD spectrum of FeHCF / Zn, 1 is the initial state, 2 is after 5 minutes of discharge, 3 is after 10 minutes of discharge, 4 is after 10 minutes of discharge and then 5 minutes of charge, 5 is after 10 minutes of discharge and then 10 minutes of charge; b is the theoretically calculated Fe III Fe III (CN)6 and [Fe II Fe II (CN)6] 2- Electrostatic potential diagram; c is the theoretical calculation of the electric field distribution of bare Zn and FeHCF / Zn;

[0029] Fig.16 The in-situ Raman test and sulfate peak diagram of the negative electrode after deposition of the Zn||Zn symmetric battery assembled in Example 4 and Comparative Experiment 2, a is the in-situ Raman test of Example 4, b is the in-situ Raman test of Comparative Experiment 2, c is the sulfate peak of Example 4, d is the sulfate peak of Comparative Experiment 2, and in c and d, 1 is 0 minutes of deposition, 2 is 10 minutes of deposition, 3 is 20 minutes of deposition, 4 is 30 minutes of deposition, 5 is 40 minutes of deposition, and 6 is 50 minutes of deposition;

[0030] Fig.17 These are the in-situ pH change diagram of the negative electrode region of the symmetrical battery in Example 4 and Comparative Experiment 2, the LSV curve of the electrode, and the in-situ EIS measurement of the negative electrode of the symmetrical battery. a is the in-situ pH change in the negative electrode region of the symmetrical battery, b is the LSV curve of the electrode, c is the in-situ EIS measurement of Example 4, and d is the in-situ EIS measurement of Comparative Experiment 2. DETAILED DESCRIPTION

[0031] Specific implementation method 1: This implementation method is a method for preparing an ultra-thin hydrophobic zinc-philic artificial solid protective layer, which is carried out according to the following steps:

[0032] 1. Preparation of FeHCF nanofilm:

[0033] The potassium ferricyanide aqueous solution is mixed with deionized water, and the dioctadecyl dimethyl ammonium bromide chloroform solution is dispersed on the liquid surface and allowed to stand to form a surfactant layer at the air-water interface, and then the ferric chloride aqueous solution is added dropwise to the solution below the surfactant layer, and reacted at room temperature to form a FeHCF nanofilm at the air-water interface, thereby obtaining a liquid containing the FeHCF nanofilm;

[0034] 2. Transfer of FeHCF nanofilm:

[0035] The substrate is vertically immersed in a liquid containing the FeHCF nanofilm, and then the substrate is slowly lifted, the FeHCF nanofilm formed at the air-water interface is transferred to the substrate, and finally dried, thereby completing the preparation method of the ultra-thin hydrophobic zinc-philic artificial solid protective layer.

[0036] The beneficial effects of this embodiment are:

[0037] This embodiment provides a new method for stabilizing the zinc metal anode by constructing an ultrathin (~16.9 nm), Zn 2+Selective and water-repellent layer. This interface engineering strategy effectively eliminates the electrode interface water layer, inhibits hydrogen evolution and corrosion, and thus overcomes the long-standing obstacle to the development of aqueous zinc batteries. The "Faraday cation pumping" mechanism generated within the FeHCF nanomembrane ensures fast and selective Zn 2+ transport while maintaining negligible water permeation, thus creating a stable, dendrite-free environment.

[0038] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that: the concentration of the potassium ferricyanide aqueous solution described in step 1 is 0.01 mol / L to 0.2 mol / L; the concentration of the dioctadecyl dimethyl ammonium bromide chloroform solution described in step 1 is 1.0 mmol / L to 2.0 mmol / L; the concentration of the ferric chloride aqueous solution described in step 1 is 0.01 mol / L to 0.2 mol / L. Others are the same as specific embodiment 1.

[0039] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the volume ratio of the potassium ferrocyanide aqueous solution to deionized water in step 1 is 1:(10-20). Other aspects are the same as specific implementation method 1 or 2.

[0040] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the volume ratio of the potassium ferrocyanide aqueous solution to the dioctadecyl dimethyl ammonium bromide chloroform solution in step 1 is 1:(0.001-0.01). Others are the same as specific embodiments 1 to 3.

[0041] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the volume ratio of the potassium ferrocyanide aqueous solution to the ferric chloride aqueous solution in step 1 is 1:(1-2). Other aspects are the same as specific embodiments 1 to 4.

[0042] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that: in step 1, the mixture is allowed to stand for 5 to 60 minutes; and in step 1, the mixture is reacted at room temperature for 20 to 48 hours. The rest is the same as specific implementation methods 1 to 5.

[0043] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that the thickness of the FeHCF nanofilm in step 1 is 10 nm to 50 nm. The rest is the same as specific embodiments 1 to 6.

[0044] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the substrate described in step 2 is a metal zinc negative electrode. The rest is the same as specific embodiments 1 to 7.

[0045] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 2, the substrate is slowly lifted at a speed of 0.01 m / s to 1 m / s; the drying in step 2 is specifically carried out at a temperature of 25° C. to 60° C. for 0.5 h to 24 h. The rest is the same as specific embodiments 1 to 8.

[0046] Specific implementation method ten: The application of the ultra-thin hydrophobic zinc-philic artificial solid protective layer in this implementation method is used as a protective layer for the zinc negative electrode in an aqueous zinc ion battery.

[0047] The following examples are used to verify the beneficial effects of the present invention:

[0048] Embodiment 1:

[0049] A method for preparing an ultra-thin hydrophobic zinc-philic artificial solid protective layer is carried out according to the following steps:

[0050] 1. Preparation of FeHCF nanofilm:

[0051] 2 mL of potassium ferricyanide (K3Fe(CN)6) aqueous solution was added to a culture dish with a diameter of 8.5 cm, and then 20 mL of deionized water was added and mixed evenly, 20 μL of dioctadecyl dimethyl ammonium bromide (DODA) chloroform solution was dispersed on the liquid surface and allowed to stand for 5 min to form a surfactant layer at the air-water interface, and then 2 mL of ferric chloride aqueous solution was added dropwise to the solution below the surfactant layer, and the reaction was carried out at room temperature for 20 h to form a FeHCF nanofilm at the air-water interface, thereby obtaining a liquid containing a FeHCF nanofilm;

[0052] The concentration of the potassium ferrocyanide aqueous solution is 0.05 mol / L; the concentration of the dioctadecyl dimethyl ammonium bromide chloroform solution is 1.8 mmol / L; the concentration of the ferric chloride aqueous solution is 0.025 mol / L;

[0053] The thickness of the FeHCF nanofilm is 16.9 nm;

[0054] 2. Transfer of FeHCF nanofilm:

[0055] The substrate was vertically immersed in the liquid of the FeHCF nanofilm, and then the substrate was slowly lifted at a speed of 0.01 m / s, and the FeHCF nanofilm formed at the air-water interface was transferred to the substrate, and finally dried at a temperature of 60°C for 0.5 h to obtain a zinc sheet (FeHCF / Zn) covered with an ultra-thin hydrophobic zinc-philic artificial solid protective layer and a copper sheet covered with an ultra-thin hydrophobic zinc-philic artificial solid protective layer;

[0056] The zinc sheet is a zinc sheet polished with sandpaper to a smooth surface; the substrate is a zinc sheet (thickness 200 μm) or a copper sheet (thickness 100 μm).

[0057] Example 2: This example is different from Example 1 in that: in step 1, 200 mL of potassium ferricyanide (K3Fe(CN)6) aqueous solution is added to a container with a size of 1.2 m×0.3 m, and then 2000 mL of deionized water is added and mixed evenly, 1000 μL of chloroform solution of dioctadecyl dimethyl ammonium bromide (DODA) is dispersed on the liquid surface and allowed to stand for 5 min, a surfactant layer is formed at the air-water interface, and then 200 mL of ferric chloride aqueous solution is added dropwise to the solution below the surfactant layer, and the reaction is carried out at room temperature for 20 h, and a FeHCF nanofilm is formed at the air-water interface to obtain a liquid containing a FeHCF nanofilm. The rest is the same as Example 1.

[0058] Example 3, preparation of Zn||Cu half-cell:

[0059] The zinc sheet (1 cm in diameter) covered with an ultra-thin hydrophobic zinc-philic artificial solid protective layer prepared in Example 1 was used as the negative electrode of the battery, the copper sheet (1 cm in diameter) covered with an ultra-thin hydrophobic zinc-philic artificial solid protective layer prepared in Example 1 was used as the positive electrode of the battery, glass fiber was used as a separator, and 80 μL of zinc sulfate electrolyte (2M) was added to prepare a CR2032 button battery.

[0060] Comparative Experiment 1: This comparative experiment is different from Example 3 in that the surfaces of the zinc sheet (thickness 200 μm, diameter 1 cm) and the copper sheet (thickness 100 μm, diameter 1 cm) are polished smooth with sandpaper, and the polished zinc sheet is used as the negative electrode of the battery, and the polished copper sheet is used as the positive electrode of the battery. The rest is the same as Example 3.

[0061] Example 4, preparation of Zn||Zn symmetric battery:

[0062] The zinc sheet (1 cm in diameter) covered with an ultra-thin hydrophobic zinc-philic artificial solid protective layer prepared in Example 1 was used as the negative and positive electrodes of the battery, glass fiber was used as a separator, and 80 μL of zinc sulfate electrolyte (2M) was added to prepare a CR2032 button battery.

[0063] Comparative Experiment 2: This comparative experiment is different from Example 4 in that the surface of the zinc sheet (1 cm in diameter) is polished smooth with sandpaper, and the polished zinc sheet is used as the negative electrode and positive electrode of the battery. The rest is the same as Example 4.

[0064] Figure 1This is a physical picture of the FeHCF nanofilm formed at the air-water interface in step 1 of Example 2, a is the overall physical picture, and b is a local enlarged picture of the edge of the FeHCF nanofilm; it can be seen from the figure that Example 2 successfully prepared a large-area continuous FeHCF nanofilm (size 1.2m×0.3m) floating on the air / water interface.

[0065] For optical microscopy testing, the FeHCF nanofilm was transferred to a silicon substrate in step 2 of Example 1; for transmission electron microscopy testing, the FeHCF nanofilm was transferred to a copper mesh substrate in step 2 of Example 1; Figure 2 Optical microscope and transmission electron microscope images of the FeHCF nanofilm prepared in step 1 of Example 1, (a) optical microscope image, (b) transmission electron microscope image; the optical and transmission electron microscope images confirm the uniformity, continuity and defect-freeness of the transferred nanofilm at the macro and micro levels.

[0066] Figure 3 XRD pattern and TEM high-resolution image of the FeHCF nanofilm prepared in step 1 of Example 1, (a) XRD image, (b) TEM high-resolution image, and the inset is an electron diffraction pattern; the X-ray diffraction (XRD) pattern shows the characteristic peaks of the face-centered cubic FeHCF phase; the high-resolution TEM image shows lattice fringes with a plane spacing of 0.49 nm, corresponding to the (200) plane; selected area electron diffraction (SAED) verifies the cubic structure.

[0067] In order to conduct element distribution, AFM, Raman and XPS full spectrum tests, in step 2 of embodiment 1, the FeHCF nanofilm is transferred to a silicon substrate; Figure 4 Element distribution map, AFM map, Raman map, and XPS full spectrum map of the FeHCF nanofilm prepared in step 1 of Example 1, (a) element distribution image, (b) AFM image, (c) Raman image, and (d) XPS full spectrum map; element mapping shows that Fe, N, and C are evenly distributed throughout the film; AFM image shows that the thickness of the synthesized nanofilm is about 16.9 nm; Raman spectrum shows that cyanide is at 2156 cm -1 and 2092cm -1 The stretching vibrations at the positions are CN- coordinated with Fe(III) and Fe(II) respectively. The full spectrum of X-ray photoelectron spectroscopy (XPS) once again confirmed the presence of carbon, nitrogen, iron, and oxygen; by X-ray photoelectron spectroscopy (XPS) peak separation of Fe 2p signals ( Fig.14 (c) further confirms the mixed state of Fe(II) / Fe(III).

[0068] The zinc sheet covered with the ultra-thin hydrophobic zinc-philic artificial solid protective layer prepared in Example 1 was used to perform infrared and contact angle tests; Figure 5The infrared images and contact angle images are as follows: (a) the infrared image of the FeHCF nanofilm prepared in step 1 of Example 1; (b) the contact angle comparison of the zinc sheet covered with the ultra-thin hydrophobic zinc-philic artificial solid protective layer prepared in Example 1 and bare Zn; the FTIR spectrum of the FeHCF nanofilm at 2087 cm -1 In addition, at 2918 cm -1 and 2850cm -1 The observed antisymmetric and symmetric stretching bands of methylene groups match those of crystalline DODABr, confirming the presence of ordered alkyl chains in the FeHCF nanofilm. The incorporation of these alkyl chains renders the FeHCF nanofilm significantly hydrophobic. As a result, FeHCF / Zn exhibits a larger contact angle (110°) compared to bare Zn (72°), reflecting an effective water-repellent interface.

[0069] Figure 6 This is a comparison chart of the deposition / stripping coulombic efficiency test of the Zn||Cu half-cell assembled in Example 3 and Comparative Experiment 1. a is the value at 10 mA / cm 2 and 1mAh / cm 2 CE diagram of Zn||Cu half-cell, b is at 5mA / cm 2 and 1mAh / cm 2 CE diagram of Zn||Cu half-cell when ; Figure 7 At 10mA / cm 2 and 1mAh / cm 2 Comparison of the voltage distribution of the Zn||Cu half-cells assembled in Example 3 and Comparative Experiment 1, a for Example 3, b for Comparative Experiment 1; at 10 mA / cm 2 and 1mAh / cm 2 In the Zn||Cu battery, the Coulombic efficiency (CE) of the bare zinc electrode suddenly dropped after only 800 cycles. In sharp contrast, the CE of the FeHCF / Zn electrode remained at 99.94% for more than 10,000 cycles. The voltage distribution of FeHCF / Zn remained stable and reduced polarization, confirming that the FeHCF layer effectively stabilized the interface and mitigated the polarization effect. Even at 5 mA / cm 2 and 1mAh / cm 2 At a lower current density of 2.5 Å, FeHCF / Zn can still operate reliably for more than 10,000 cycles with an average CE of 99.91%.

[0070] To conduct DOD testing, the FeHCF nanofilm was transferred onto zinc foil in step 2 of Example 1, and a Zn||Zn symmetric cell was formed using Example 4 and Comparative Experiment 2; Figure 8This is a comparison chart of the cycle test of the Zn||Zn symmetric battery assembled by transferring the FeHCF nanofilm to zinc foil in Example 4 and Comparative Experiment 2, a at 1 mA / cm 2 and 1mAh / cm 2 Cyclic performance under 2 mA / cm 2 and 10mAh / cm 2 DOD cycle performance under 1 mA / cm2 for symmetric Zn||Zn battery 2 and 1mAh / cm 2 Bare Zn fails after only 146 hours due to uncontrolled dendrite growth and side reactions, while FeHCF / Zn achieves stable cycling for more than 2000 hours with a low overpotential (38 mV vs. 60 mV for bare Zn), extending the operating life by about 14 times. 2 and large area capacity of 10 mAh / cm 2 Under the condition of (~60% DOD), the FeHCF / Zn electrode maintains stable cycling for 160 h, while the bare zinc anode fails rapidly.

[0071] At the same time, the Zn||Zn symmetrical battery assembled in Example 4 and Comparative Experiment 2 was tested as follows: 2 and a higher current density of 5 mA / cm 2 Bare Zn shorted after 125 hours, while FeHCF / Zn lasted for more than 3200 hours without failure, further demonstrating the special protective effect of FeHCF nanofilm. 2 And higher current density is 50mA / cm 2 When the bare zinc runs for less than 60 hours, the FeHCF / Zn runs for about 240 hours without any failure, indicating that the FeHCF nanofilm has a protective effect under high current density. 2 and low current density 1mA / cm 2 Under the above conditions, bare zinc short-circuited after 50 hours, while FeHCF / Zn cycled for 400 hours, with a lifespan about 8 times that of bare zinc. In summary, the FeHCF nanofilm improves the stability, reversibility, and cycle life of the metallic zinc anode. By inhibiting dendrite growth, minimizing side reactions, and ensuring uniform Zn 2+ deposited, FeHCF / Zn interface greatly enhances the prospects of high-performance, durable, and safe Zn-based energy storage systems.

[0072] In order to observe the morphological evolution of the electrode interface during zinc deposition and stripping, the current density was 40 mA / cm 2 and capacity density of 6 mAh / cm 2Under the conditions, the Zn||Cu half-cells assembled in Example 3 and Comparative Experiment 1 were subjected to cycle tests, and then the positive FeHCF / Cu and bare Cu electrodes were subjected to in-situ optical microscopy tests and zinc thickness and deposition / stripping time tests. The test results are shown in Figure 2. Fig. 9 and Fig.10 ;

[0073] Fig. 9 In-situ optical microscope images of zinc deposition / stripping of FeHCF / Cu and bare Cu after cycling of the Zn||Cu half-cell assembled in Example 3 and Comparative Experiment 1, a is bare Cu, b is FeHCF / Cu; the FeHCF / Cu electrode always shows dense and uniform zinc deposition without obvious dendrite formation, confirming the stable Zn 2+ In contrast, the bare Cu electrode gradually forms irregular protrusions and aggregated deposits, which remain even after stripping, reflecting the continuous inhomogeneous electrodeposition and stripping process.

[0074] Fig.10 The thickness of zinc deposited on FeHCF / Cu and bare Cu after cycling and the deposition / stripping time of the Zn||Cu half-cell assembled in Example 3 and Comparative Experiment 1; quantitative comparison shows that the growth density of zinc on the FeHCF / Cu electrode is higher and more controllable. 2 (corresponding to 6mAh / cm 2 ) after 540 seconds of electrodeposition under 400 μm of ionizing heat, the FeHCF / Cu electrode produced a zinc layer only 18.1 μm thick - close to the theoretical value (Theoretical curve in the figure), while the bare Cu electrode produced a thicker (95.5 μm) and more uneven layer. During the subsequent stripping process, the FeHCF-based electrode stripped the deposited zinc cleanly and uniformly, while the bare electrode surface remained rough with incomplete stripping and residual dendritic structures. These observations indicate that the FeHCF nanofilm not only facilitates efficient and compact zinc deposition, but also ensures uniform and reversible stripping.

[0075] Example 1 Step 2 The prepared FeHCF nanofilm was transferred to a titanium foil and a battery was assembled in an electrolytic cell. One side was a zinc sheet (area 10×10 cm2) covered with an ultra-thin hydrophobic zinc-philic artificial solid protective layer prepared in Example 1. 2 , thickness 200 μm), one side is a titanium foil (area 10×10 cm 2 , thickness 10 μm), add 1L of zinc sulfate electrolyte (2M), and at a current density of 20 mA / cm 2Under the conditions of , the zinc foil was deposited on the titanium foil for 2.5 hours, the morphology of the zinc foil deposited on the titanium foil was observed, and the zinc foil was peeled off to test its mechanical strength. The above process is the experimental group. During the peeling process, the FeHCF nanofilm was peeled off and attached to the surface of the zinc foil; the control group is pure titanium foil. Fig.11 Figures 3 and 4 are the morphology and mechanical strength test diagrams of zinc foil after deposition of FeHCF nanofilms prepared in Example 1 attached to titanium foil (experimental group) and pure titanium foil (control group), a is a schematic diagram and a physical picture of the peeling of zinc foil deposited on the surface of the titanium foil of the experimental group, b is a physical picture of a large area (10 cm×10 cm) of zinc foil deposited on the surface of the titanium foil of the experimental group after peeling, c is a physical picture of the zinc foil deposited on the surface of the titanium foil of the experimental group after peeling and folding, d is a physical picture of the zinc foil deposited on the surface of the titanium foil of the control group after peeling and folding; a and b show that the zinc deposited on the titanium foil can be cleanly peeled off, which indicates that the FeHCF nanofilm can effectively achieve uniform and dense zinc deposition on a macro scale; c and d are mechanical strength tests of the zinc foil peeled off after deposition, and the mechanical strength of the zinc foil with a protective layer is higher and can be bent at will, while the mechanical strength of the zinc foil without a protective layer is low, and cracks appear after bending.

[0076] At 10mA / cm 2 and 1mAh / cm 2 Under the conditions of , the Zn||Zn symmetric batteries assembled in Example 4 and Comparative Experiment 2 were cycled for 500 cycles, and then the negative electrode was subjected to SEM testing. Fig.12 The scanning electron microscope images of the negative electrode of the Zn||Zn symmetric battery assembled in Example 4 and Comparative Experiment 2 after cycling, a and b are for Example 4, c and d are for Comparative Experiment 2; as shown in c and d, due to uneven zinc deposition and severe side reactions, the bare zinc negative electrode has an uneven morphology with obvious dendrites and pits. In contrast, the surface of the zinc electrode with a protective layer remains dense and uniform after cycling, with no obvious Zn protrusion, as shown in a and b, indicating that the uniform FeHCF layer can guide the lateral uniform Zn deposition, confirming the role of the FeHCF nanofilm in inhibiting dendrites.

[0077] Since the Prussian blue material itself has the characteristic of electrochromism, that is, under the action of an electric field, a redox reaction occurs, electrons are gained or lost, and the color of the material changes. In order to visually see that it has redox ability, the FeHCF nanomembrane prepared in step 1 of Example 1 was filtered to obtain membrane powder. The FeHCF powder was evenly mixed with PVDF binder at a mass ratio of 9:1, and then coated on a zinc foil (area 1×1 cm) using a scraper. 2 , thickness 10 μm), the obtained zinc foil with FeHCF powder attached was electrolyzed in an electrolytic cell with a zinc sheet (area 1×1 cm 2 ) were assembled into a battery, 5 mL of zinc sulfate electrolyte (2 M) was added, and the2 and 3mAh / cm 2 The zinc foil attached with FeHCF powder was cycled every 5 minutes, and a photo was taken of the zinc foil attached with FeHCF powder. The XPS test was performed on the zinc foil attached with FeHCF powder. The test results are shown in the figure. Fig.13 and Fig.14 .

[0078] Fig.13 The zinc foil attached with FeHCF powder prepared in Example 1 has reversible color change during zinc deposition and stripping; a is uncycled; b is 2.5 mA-hour deposited at a current of 20 mA; c is 5 mA-hour deposited at a current of 20 mA; d is 5 mA-hour deposited first and then 2.5 mA-hour stripped at a current of 20 mA; e is 5 mA-hour deposited first and then 5 mA-hour stripped at a current of 20 mA; It can be seen from the figure that the color of FeHCF gradually changes from dark green to bright blue during the deposition process, and gradually returns to dark green during stripping, indicating that electron gain and loss do occur during deposition and stripping, and it has redox properties.

[0079] Fig.14 The XPS spectra of FeHCF prepared in Example 1 during zinc deposition and stripping and the Fe 2p XPS spectra of the FeHCF nanofilm without circulation, a is FeHCF after deposition for 15 minutes, b is FeHCF after deposition for 15 minutes and then stripping for 15 minutes, and c is the Fe 2p XPS spectrum of the FeHCF nanofilm prepared in step 1 of Example 1 without circulation; it can be seen from the figure that the film contains Fe 3+ and Fe 2+ During the deposition process, Fe 2+ The content increased significantly, indicating that some Fe 3+ Reduced to Fe 2+ , which can produce a net negative charge distribution on the zinc anode surface, which can spontaneously attract the positively charged Zn 2+ , so that Zn 2+ Flux homogenization, suppression of Zn 2+ Aggregation. In the process of deposition followed by stripping, Fe 3+ The content increased significantly, indicating that the FeHCF protective layer is reversible and is expected to become a fast ion conductive SEI layer on the zinc electrode.

[0080] To verify the structural stability, the Zn||Zn symmetrical battery assembled in Example 4 was subjected to XRD test after charge and discharge cycles. During the charge and discharge cycles, the XRD test was performed at 20 mA / cm 2 The battery was stopped after the four processes of discharging for 5 minutes, discharging for 10 minutes, discharging for 10 minutes and then charging for 5 minutes, and discharging for 10 minutes and then charging for 10 minutes under the current, and the negative electrode was tested by XRD. Fig.15XRD diagram, theoretically calculated electrostatic potential diagram and theoretically calculated electric field distribution of the negative electrode of the Zn||Zn symmetrical battery assembled in Example 4 after charge and discharge cycles; a is the XRD spectrum of FeHCF / Zn, 1 is the initial state, 2 is after 5 minutes of discharge, 3 is after 10 minutes of discharge, 4 is after 10 minutes of discharge and then 5 minutes of charge, 5 is after 10 minutes of discharge and then 10 minutes of charge; b is the theoretically calculated Fe III Fe III (CN)6 and [Fe II Fe II (CN)6] 2- b and c are theoretical calculations. First, the electrostatic potential containing trivalent iron and divalent iron is calculated. It can be seen intuitively that the overall negative charge is increased when trivalent iron is converted to divalent iron. The adsorption energy of zinc ions on FeHCF with trivalent iron and divalent iron is also calculated. Both of them show strong attraction to zinc ions, which is beneficial to Zn. 2+ Finally, in the electric field simulation, it can be seen that the protective layer indeed makes the electric field at the metal zinc electrode-electrolyte interface uniform.

[0081] In order to explore the changes in the interface structure of the metal zinc electrode during the deposition process, the 2 and 1mAh / cm 2 Next, the negative electrode in-situ Raman test was performed on the Zn||Zn symmetric battery assembled in Example 4 and Comparative Experiment 2. Fig.16 In-situ Raman test and sulfate peak diagram of the negative electrode during the deposition process of the Zn||Zn symmetric battery assembled for Example 4 and Comparative Experiment 2, a is the in-situ Raman test of Example 4, b is the in-situ Raman test of Comparative Experiment 2, c is the sulfate peak of Example 4, d is the sulfate peak of Comparative Experiment 2, and 1 in c and d is 0 minutes of deposition, 2 is 10 minutes of deposition, 3 is 20 minutes of deposition, 4 is 30 minutes of deposition, 5 is 40 minutes of deposition, and 6 is 50 minutes of deposition; the intensity of sulfate at the electrode interface can characterize the transport of zinc ions at the electrode electrolyte interface. During the deposition process, due to the hydrogen evolution reaction, the hydroxide concentration will increase, and combine with sulfate to form by-products, resulting in a decrease in sulfate concentration. It can be seen from Figures a and b that the peak intensity of sulfate in the experimental group with a protective layer is stable, basically unchanged, and the peak position has no shift, indicating that the transport of zinc ions at the electrode electrolyte interface is stable, reducing the occurrence of side reactions. It can be seen from Figures c and d that the fitting belongs to SO4 2-The Raman spectrum of the stretched vibration can be integrated into two different peaks, namely the solvent separation ion pair SSIPs and the contact ion pair CIPs. By comparison, it can be found that the peak area of ​​the SSIP on the surface of the protected zinc negative electrode gradually increases, proving that it inhibits the occurrence of side reactions.

[0082] Monitoring Zn||Zn symmetric cells in Zn 2+ In situ pH change during ion deposition at 10 mA / cm 2 and 1mAh / cm 2 The Zn||Zn symmetrical battery assembled in Example 4 and Comparative Experiment 2 was cycled, and the pH of the negative electrode region was recorded once every cycle until one minute of discharge. The test results are as follows: Fig.17 Figure a in the middle.

[0083] Water erosion can trigger hydrogen evolution reaction. In order to evaluate the effect of FeHCF layer on the inhibition of hydrogen evolution HER, a three-electrode system was used. In Example 1, step 2, the prepared FeHCF nanofilm was transferred to titanium foil. In a 1M Na2SO4 aqueous solution, the polarization behavior was characterized by linear sweep voltammetry (LSV) at 1mV / s, wherein the titanium foil coated with FeHCF nanofilm or pure titanium foil was used as the working electrode, and Ag / AgCl was used as the reference electrode. The test results are shown in FIG. Fig.17 Figure b.

[0084] To investigate the electrochemical stability of the interface, in-situ EIS tests were performed on the Zn||Zn symmetrical cells assembled in Example 4 and Comparative Experiment 2. 2 and 1mAh / cm 2 Under this condition, the negative electrode is subjected to an EIS test every 60 cycles. The test results are as follows: Fig.17 Figures c and d.

[0085] Fig.17 The in-situ pH change diagram of the negative electrode area of ​​the symmetrical battery in Example 4 and Comparative Experiment 2, the LSV curve of the electrode, and the in-situ EIS measurement of the negative electrode of the symmetrical battery, a is the in-situ pH change of the negative electrode area of ​​the symmetrical battery, b is the LSV curve of the electrode, c is the in-situ EIS measurement of Example 4, and d is the in-situ EIS measurement of Comparative Experiment 2. As can be seen from a, the pH value of the exposed Zn electrode rises rapidly from 3.5 to 5.92, which is due to the strong hydrogen evolution reaction and the formation of by-products. On the contrary, the pH value at the FeHCF / Zn interface rises from 3.47 to 5.25, and the rising trend is relatively slow, indicating that the side reactions and hydrogen evolution reactions are effectively suppressed, indicating that the FeHCF protective layer effectively isolates the direct contact between the aqueous electrolyte and the zinc negative electrode. As can be seen from b, in the absence of Zn 2+In the case of deposition, it can be seen that the presence of FeHCF significantly increases the electrochemical window, increasing the HER potential from -123 mV to -139 mV. As can be seen from c and d, the interfacial charge transfer resistance of FeHCF / Zn is generally smaller than that of bare Zn, which proves that the FeHCF interface layer promotes the electrochemical kinetics of the Zn negative electrode. According to the test data of bare zinc, it can be found that the interfacial charge transfer resistance of bare zinc has increased and dropped in a leap-like manner with the increase in the number of cycles. This may be due to the uneven deposition of Zn by bare zinc during the deposition process, which makes the EIS curve during the deposition process unstable, as well as the generation and falling of by-products. In contrast, FeHCF / Zn is more stable during the cycle. It proves that the protective layer can reduce the occurrence of side reactions and make zinc ions deposit evenly.

[0086] principle:

[0087] First, during cycling, the FeHCF nanofilm actively responds to changes in electrode potential and maintains dynamic electrochemical regulation. The color change between dark green (reduced state) and blue (oxidized state) during zinc deposition and stripping clearly shows its reversible redox characteristics. Although the ultrathin (16.9 nm) layer undergoes redox transitions, its contribution to the total areal capacity is still negligible (0.58 μAh / cm 2 ), which ensures that the active negative electrode capacity is not affected. XPS analysis during zinc deposition and stripping shows that Fe 3+ Ions in Zn 2+ Reversible reduction to Fe during deposition 2+ , in Zn 2+ Oxidized back to Fe during stripping 3+ This reversible redox transition provides a tunable interfacial charge environment: upon Zn deposition, the FeHCF layer develops a net negative charge, electrostatically attracting Zn 2+ , and regulates its spatial distribution at the interface. This electrostatic gating promotes uniform Zn 2+ The FeHCF surface can effectively reduce the concentration polarization and uncontrolled lateral ion diffusion, which helps to reduce the formation of dendrites. In addition, the negatively charged FeHCF surface repels sulfate anions and inhibits the formation of by-products. 2+ Reoxidized to Fe 3+ This negative charge is reduced, making Zn 2+ The cation pumping is a process that allows for the release of cations and improves the stripping efficiency. XRD measurements confirm that this redox-dominated Faraday “cation pumping” is structurally reversible and that FeHCF maintains its crystalline framework during cycling. Theoretical calculations show that both the oxidized and reduced states exhibit higher Zn 2+ adsorption energy, thus intrinsically favoring Zn 2+Electric field simulations further demonstrated that the FeHCF layer homogenizes the interfacial field, reducing the number of sites that could nucleate dendrites. This Faradaic cation pumping mechanism, facilitated by the open three-dimensional FeHCF lattice and its redox-active Fe centers, ensures abundant, consistent, and rapid Zn transport. 2+ As a result, zinc is deposited as a dense, uniform layer rather than forming protrusions, which significantly suppresses dendrite growth and ensures stable, long-term electrode operation.

[0088] Secondly, to further clarify the stability of the FeHCF layer on the interface, in situ Raman spectroscopy was used to monitor the sulfate (SO4 2- ) behavior. On the FeHCF / Zn electrode, ν-SO4 2- The band intensity of ν-SO4 increases slightly initially and then remains relatively stable throughout the deposition process. 2- The intensity decreases rapidly, reflecting the rapid depletion of sulfate and the unstable interfacial conditions. Because zinc ions in aqueous zinc sulfate solutions can exist in the form of solvent-separated ion pairs (SSIPs) and contacted ion pairs (CIPs), the change in their ratio provides insights into the kinetics of ion transport. On FeHCF / Zn, the SSIP ratio increases significantly from 38.0% to 69.3% during deposition, indicating that the negatively charged and hydrophobic FeHCF surface promotes the selective Zn transport. 2+ Ion pumping and repelling sulfate anions maintain a good SSIP environment. In contrast, the bare Zn electrode does not maintain such a good SSIP / CIP ratio. FeHCF / Zn (55.6 kJ / mol)Zn 2+ This selective ion transport is further confirmed by the reduced activation energy for desolvation, confirming the enhanced Zn2+ ion transport kinetics. Meanwhile, the hydrophobic alkyl chains repel water molecules, reducing water-induced side reactions and broadening the electrochemical stability window. In situ pH monitoring revealed a milder pH increase for the FeHCF / Zn electrode compared with bare Zn, implying effective HER inhibition. In situ electrochemical impedance spectroscopy (EIS) further confirmed that FeHCF / Zn consistently maintained a lower and more stable interfacial resistance during long-term cycling, while bare Zn faced escalating resistance, which could be caused by irregular Zn deposition and byproduct accumulation. More importantly, the fitted EIS showed a stable membrane resistance with no signs of water layer formation. Overall, these observations suggest that the FeHCF nanomembrane ensures a well-water-repellent and ion-selective interface, effectively mitigating harmful side reactions and maintaining superior electrochemical stability.

[0089] FeHCF nanofilm has the advantages of preventing the zinc electrode from contacting with water and Zn 2+ Selective dual effect: Under the action of these two protections, FeHCF nanofilm can inhibit dendrites, by-products, etc., and improve the cycle stability and cycle life of the battery.

[0090] It can be seen that the embodiment constructs ultra-thin (~16.9nm), Zn 2+ The selective and water-repellent layer stabilizes the Zn anode. This interface engineering strategy effectively eliminates the water layer at the electrode interface, inhibits hydrogen evolution and corrosion, and thus overcomes the long-standing obstacle in the development of aqueous Zn metal batteries. The "Faraday cation pumping" mechanism generated within the FeHCF framework ensures fast and selective Zn 2+ transport while maintaining negligible water permeation, thus creating a stable, dendrite-free environment. The benefits of this design are obvious, and remarkable electrochemical performance can be achieved. 2 and 1mAh / cm 2 The results show that the CE of Zn anode is 99.91% with an average duration of more than 10,000 deposition / stripping cycles, far exceeding the stability of conventional Zn anode.

Claims

1. A method for preparing an ultra-thin hydrophobic zinc-philic artificial solid protective layer, characterized in that It is carried out in the following steps:

1. Preparation of FeHCF nanofilm: The potassium ferricyanide aqueous solution is mixed with deionized water, and the dioctadecyl dimethyl ammonium bromide chloroform solution is dispersed on the liquid surface and allowed to stand to form a surfactant layer at the air-water interface, and then the ferric chloride aqueous solution is added dropwise to the solution below the surfactant layer, and reacted at room temperature to form a FeHCF nanofilm at the air-water interface, thereby obtaining a liquid containing the FeHCF nanofilm; 2. Transfer of FeHCF nanofilm: The substrate is vertically immersed in a liquid containing the FeHCF nanofilm, and then the substrate is slowly lifted, the FeHCF nanofilm formed at the air-water interface is transferred to the substrate, and finally dried, thereby completing the preparation method of the ultra-thin hydrophobic zinc-philic artificial solid protective layer.

2. The method for preparing an ultra-thin hydrophobic zinc-philic artificial solid protective layer according to claim 1, characterized in that The concentration of the potassium ferrocyanide aqueous solution described in step 1 is 0.01 mol / L to 0.2 mol / L; the concentration of the dioctadecyl dimethyl ammonium bromide chloroform solution described in step 1 is 1.0 mmol / L to 2.0 mmol / L; the concentration of the ferric chloride aqueous solution described in step 1 is 0.01 mol / L to 0.2 mol / L.

3. The method for preparing an ultra-thin hydrophobic zinc-philic artificial solid protective layer according to claim 1, characterized in that The volume ratio of the potassium ferrocyanide aqueous solution to deionized water in step 1 is 1:(10-20).

4. The method for preparing an ultra-thin hydrophobic zinc-philic artificial solid protective layer according to claim 1, characterized in that The volume ratio of the potassium ferrocyanide aqueous solution to the dioctadecyl dimethyl ammonium bromide chloroform solution described in step 1 is 1:(0.001-0.01).

5. The method for preparing an ultra-thin hydrophobic zinc-philic artificial solid protective layer according to claim 1, characterized in that The volume ratio of the potassium ferrocyanide aqueous solution to the ferric chloride aqueous solution described in step 1 is 1:(1-2).

6. The method for preparing an ultra-thin hydrophobic zinc-philic artificial solid protective layer according to claim 1, characterized in that In step 1, the mixture is allowed to stand for 5 to 60 minutes; in step 1, the mixture is reacted at room temperature for 20 to 48 hours.

7. The method for preparing an ultra-thin hydrophobic zinc-philic artificial solid protective layer according to claim 1, characterized in that The thickness of the FeHCF nanofilm described in step 1 is 10nm to 50nm.

8. The method for preparing an ultra-thin hydrophobic zinc-philic artificial solid protective layer according to claim 1, characterized in that The substrate described in step 2 is a metal zinc negative electrode.

9. The method for preparing an ultra-thin hydrophobic zinc-philic artificial solid protective layer according to claim 1, characterized in that In step 2, the substrate is slowly lifted at a speed of 0.01 m / s to 1 m / s; the drying in step 2 is specifically carried out at a temperature of 25° C. to 60° C. for 0.5 h to 24 h.

10. Use of the ultra-thin hydrophobic zinc-philic artificial solid protective layer prepared as claimed in claim 1, characterized in that It is used as a protective layer for the zinc anode in aqueous zinc-ion batteries.

Citation Information

Patent Citations

  • Rechargeable metal hydride air battery

    CN101752628A

  • Preparation method of electrode material for aqueous zinc ion hybrid energy storage device

    CN111916709A

  • Preparation method and application of zinc-loving hydrophobic interface nano film

    CN116936726A

  • Metal organic frame reverse osmosis membrane and preparation method therefor

    WO2019179082A1